Thyroid Function Status in Patient with Iron Deficiency Anaemia in A Tertiary Care Hospital of Lalitpur, Nepal - Bhattarai, Binita; Bataju, Mahima; Niraula, Apeksha (Med Phoenix, 2023)
Introduction: Studies have found that iron deficiency anaemia (IDA) impairs thyroid hormone metabolism. The prevalence of thyroid dysfunction in adults in the general population ranges from 1 to 10 percent, and is even higher in selected groups. Thus, in this study we would like to see thyroid function status in people with IDA. Materials and Methods: It was Laboratory based cross sectional study conducted in the Department of Biochemistry of a tertiary care hospital of KIST Medical College and Teaching Hospital, Lalitpur, Nepal. Secondary data of 162 patients available in laboratory database of 3 years’ duration from August 2018 to August 2021 were taken. All Patients diagnosed with IDA whose thyroid profile was also done were included in the study. Data were entered in Microsoft Excel. Statistical analysis was performed using version 29 of the Statistical Package for Social Sciences (SPSS Inc, Chicago IL, USA). Results: Among 162 IDA patients, 86.4% (n=140) were females and 13.62% (n=22) were males. Age ranged widely from 19 to 88 years and median age was 38 years. Out of 162 patients most of the patients 68.5% were euthyroid, 8.7% had euthyroid hypothyroxinemia, 7.4% had primary hypothyroidism,3.7% had subclinical hypothyroidism, 3.1% had secondary hypothyroidism, 1.2% had primary hyperthyroidism, 1.2% had T3 toxicosis, 0.6% had euthyroid hyperthyroxinemia. Based on multiple independent KW test, relationship between category of thyroid disorders and iron profile as well as thyroid disorder and Hb level were found not to be statistically significant. No category of thyroid dysfunction was associated with value of haemoglobin level or severity of anaemia. Irrespective of category of thyroid profile including euthyroid, hypothyroid and hyperthyroid, no category is particularly associated with IDA. Conclusion: In patients with IDA, there is no significant association between Hb level or severity of iron deficiency irrespective of patient being euthyroid, hypothyroid or hyperthyroid.